Doktrin Res Ipsa Loquitur Pada Perlindungan Konsumen - Angela, Irene Maria; Suryamah, Aam; Yuanitasari, Deviana (Widya Yuridika, 2024)
Economic growth in Indonesia can be encouraged by increasing consumer confidence. In the event of a violation of consumer rights, consumers have the right to claim compensation from business actors, but in fact, consumers and business actors have an unequal position. Consumers have difficulties in terms of civil evidence. An imbalance in the distribution of the burden of proof is an injustice for the disputing parties. The research was conducted using normative juridical research methods and comparative research methods, namely research methods carried out by studying secondary data and library materials and approaches to comparing the laws of one country with the laws of other countries. This research was conducted through library research and field research to enrich the sources. The results of further research are described in descriptive writing that relates the problem to legal theory in evaluating the practices carried out by research objects. There are 2 conclusions from the research results. First, that the position of the re ipsa loquitur doctrine in the principle of proof in consumer protection cases is closely related to the evidence imposed by judges on business actors as parties who have responsibility for the products consumed by consumers as well as those who suffer less losses to provide more justice for consumers. and in line with the principle of proof contained in UUPK and the second conclusion is that the res ipsa loquitur doctrine can be applied in cases of consumer protection if it fulfills the elements that are the requirements of the application of the re ipsa loquitur doctrine.